2011
DOI: 10.1111/j.1365-2834.2011.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Role stress among first-line nurse managers and registered nurses - a comparative study

Abstract: The implication for nursing management shows the needs for a work environment for both F-LNMs and RNs that includes high job control and good managerial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 24 publications
2
42
1
2
Order By: Relevance
“…Ainda que os enfermeiros gerentes possuam maior controle sobre seu trabalho, o que pode camuflar o estresse, apresentam carga de trabalho maior, ritmo laboral mais acelerado e níveis elevados de exigências psicológicas, aumentando sua vulnerabilidade ao adoecimento quando comparados aos enfermeiros assistenciais (2) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ainda que os enfermeiros gerentes possuam maior controle sobre seu trabalho, o que pode camuflar o estresse, apresentam carga de trabalho maior, ritmo laboral mais acelerado e níveis elevados de exigências psicológicas, aumentando sua vulnerabilidade ao adoecimento quando comparados aos enfermeiros assistenciais (2) .…”
Section: Discussionunclassified
“…O enfermeiro, na condição de gerente do cuidado, possui perspectiva única sobre o atendimento ao paciente e operações hospitalares, e está na linha de frente desses serviços de saúde (1)(2) . No entanto, esses profissionais são submetidos a vários riscos ocupacionais, principalmente os psicossociais (3)(4) .…”
Section: Introductionunclassified
“…Lindholm (2006) tested Karasek's model in a sample of Swedish nurse managers exposed to high job demands and showed they had a significantly higher likelihood of high work stress. Johansson et al (2013) compared FLMs and staff nurses and found they experienced similar levels of job demands but suggested that FLMs were better able to cope with high-demand job situations because of relatively high work control. We found no studies of FLM job strain where job strain was measured as a continuous variable.…”
Section: Job Strainmentioning
confidence: 96%
“…Prolonged job strain may contribute to burnout, mental and physical illnesses, ineffective performance, absenteeism, reduced organizational commitment, and turnover (Karasek, 1979;Karasek and Theorell, 1990). Although it seems reasonable that managers would have higher job control than other groups such as direct care nurses (Johansson et al, 2013), numerous stressors including recurring organizational restructuring, staff shortages, shrinking resources but increasing pressures to provide faster and improved services, growing government regulatory demands, and significant time pressures in today's dynamic healthcare context may severely limit FLM perceptions of control (Kath et al, 2013;Shirey et al, 2010;Wong et al, 2014). Given the importance of the FLM role to creating healthy work environments, optimal staff work outcomes and patient care quality, and the future recruitment and retention of effective FLMs, attention must be directed to understanding manager job strain and the creation of satisfying working conditions to minimize role stress.…”
Section: Introductionmentioning
confidence: 98%
“…Managers also experience higher control, higher autonomy, more influence, more freedom at work, 4,5,7,8 and more social support than subordinates. 4,9 Managers are generally found to have better health than subordinates. [10][11][12][13] Some studies have also found that managers experience less stress than subordinates.…”
Section: Introductionmentioning
confidence: 99%